The Relationship Between Self-Confidence And Entrepreneurial Motivation Of Culinary Students At Smk Negeri 2 Bukittinggi - Adira, Elsa; Yulastri, Asmar; Syarif, Wirnelis; Siregar, Juliana (Universitas Negeri Padang, 2024)
This research was motivated by the low motivation of entrepreneurial students majoring in Culinary at SMK Negeri 2 Bukittinggi. This is assumed because students feel less confident and afraid of failure to open a business. The purpose of this study is to describe: 1) student self-confidence, 2) student entrepreneurial motivation, and 3) analyze the relationship between self-confidence and entrepreneurial motivation of SMK Negeri 2 Bukittinggi Culinary students. This type of research uses quantitative methods with a correlational approach. The population of this study was 185 students culinary SMK Negeri 2 Bukittinggi. The sampling technique uses the Proportionate Random Sampling technique, a sample of 65 people consisting of 33 class XI people and 32 class XII people. Data is collected by distributing questionnaires through google forms that have been tested for validity and reliability. Data analysis uses descriptive analysis and correlational analysis. The results showed that: 1) the level of self-confidence was in the medium category with a range of 114 - 122 (35.38%), 2) the level of entrepreneurial motivation was in the medium category with a medium range of 89 - 98 (41.5%), 3) there was a positive and significant relationship between self-confidence and entrepreneurial motivation with a correlation value of rxy 0.774 which was considered strong and a Tcalculate value (9.697) > Ttable (1.669). This means that the lower the self-confidence, the motivation for entrepreneurship is also low, on the contrary, the higher the confidence, the higher the motivation for entrepreneurship students